Orally Administered Prosochit®-Based Nanoparticles of Insulin Ameliorates Alloxan-Induced Diabetes in Rats - Emmanuel O. Olorunsola; Koofreh G. Davies; Enomfon B. Essien; Mfonobong F. Alozie; Musiliu O. Adedokun; Fakhrul Ahsan (MDPI AG, 2022)
This work was aimed to assess the antidiabetic effect of orally administered Prosochit®-based nanoparticles of insulin in an animal model. Five batches of insulin-loaded nanoparticles were prepared as dry water-in-oil-in-water emulsions using different emulsifiers (prosopis gum, Prosochit® 201, Prosochit® 101, Prosochit® 102, and chitosan) for the outer emulsion. Unloaded Prosochit® 101-based nanoparticles were also formulated. The morphology and size distribution of the nanoparticles were studied using a scanning electron microscope and Zetasizer. Forty alloxan-induced diabetic Wistar rats were divided into eight groups. The different groups were administered daily with different formulations (unloaded nanoparticles, the 5 loaded nanoparticles equivalent to 50 IU insulin per kg, purified water, and Actrapid) for 14 days. Blood glucose level was monitored and determined over 24 h. Fasting blood sugar was also taken on days 3, 5, 7, and 14. A graph of the percent blood glucose level relative to time 0 h was plotted against time. The particles showed a water-in-oil-in-water constitution. Both the drug-loaded and the unloaded Prosochit®-based nanoparticles were of nano dimension. There was a significant difference (p < 0.0001) in the antidiabetic effects of all insulin-loaded nanoparticles compared with the negative control. There was no significant difference across the insulin-loaded nanoparticles of prosopis gum, Prosochit® 201, Prosochit® 102, and chitosan while the insulin-loaded Prosochit® 101 nanoparticles showed the best activity, which is comparable to subcutaneous insulin, reducing blood glucose levels to 32.20 ± 3.79%. All the oral Prosochit®-based insulin nanoparticles are characterized by appreciable antidiabetic activity with the activity of Prosochit® 101-based nanoformulation being comparable to that of the subcutaneous insulin.